Advances in biomaterials as a retinal patch for the repair of rhegmatogenous retinal detachment - Zheng, Chuanzhen; Wen, Dejia; Xu, Kejia; Zhang, Xiaomin; Ren, Xinjun; Li, Xiaorong (Frontiers in Bioengineering and Biotechnology, 2022)
Rhegmatogenous retinal detachment (RRD) is the most common retinological emergency that can cause blindness without surgical treatment. RRD occurs when liquefied vitreous accumulates between the neurosensory retina and the retinal pigment epithelium via retinal breaks, which are caused by the separation of the vitreous from the retina with aging. Currently, the main treatment option is pars plana vitrectomy, which involves surgical removal of the vitreous and subsequent filling of the vitreous cavity with long-lasting substitutes (expansile gas or silicon oil) to prevent the connection between the subretinal space and the vitreous cavity through the breaks. However, the postoperative face-down position and the not very satisfactory first retinal reattachment rate place a heavy burden on patients. With the development of technology and materials engineering, researchers have developed biomaterials that can be used as a retinal patch to seal retinal breaks and prevent the connection of subretinal space and vitreous cavity via breaks, thus replacing the long-lasting vitreous substitutes and eliminating the postoperative face-down position. Preclinical studies have demonstrated that biomaterial sealants have enough biocompatibility and efficacy in the in vitro and in vivo experiments. Some sealants have been used in clinical trials on a small scale, and the results indicate promising application prospects of the biomaterial sealants as retinal patches in the repair of RRD. Herein, we review the recent advances in biomaterials as retinal patches for the repair of RRD, focusing on the biomaterial categories, methods, and procedures for sealing retinal breaks, as well as their biocompatibility and efficacy, current limitations, and development perspectives.